HUBUNGAN PROFIL BIOGRAFI DENGAN KEMAMPUAN MENAMAI PADA PASIEN AFASIA DI RUMAH SAKIT PEMERINTAH - Liza Laela Abida; Nur Fitri Ayu Pertiwi; Hafidz Tri Antoro AJi pratomo (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Background: Language disorder is a disturbance of understanding or disruption of the use of oral or writing symbol system or other symbol system. Inability in content or language content is part of a categorized aphasia as difficulty finding words, naming an object and categorizing. One of the prognostic factors that affects the recovery process in aphasia patients is a biographical profile consisting of gender, age, and educational status . Objective: to know the relationship between biographical profiles and naming abilities in Aphasia patients at Government Hospital. Method: This research is a quantitative research by using Rule Of Thumb sampling technique. Respondents in this study amounted to 30 respondents. The statistical test used was Spearman'rho Test and Mann – Whitney test. Results: The results of Spearman's rho test between age and naming ability obtained sig 0. 265 with r value or correlation - 0. 210. Mann Whitney test results between the gender with the ability to name the results obtained sig 0. 088. Mann Whitney test results between the status of education with the ability to name the results obtained sig 0. 490. Conclusions: There is no association between biographical profiles and the ability to name in patients with Aphasia